Gathering a Euclidean Closed Chain of Robots in Linear Time and Improved Algorithms for Chain-Formation - Castenow, Jannik; Harbig, Jonas; Jung, Daniel; Knollmann, Till; Meyer auf der Heide, Friedhelm (Theoretical Computer Science)
Keywords: General Computer Science; Theoretical Computer Science

Realization of a Multi-Output Quantum Pulse Gate for Decoding High-Dimensional Temporal Modes of Single-Photon States - Serino, Laura; Gil López, Jano; Stefszky, Michael; Ricken, Raimund; Eigner, Christof; Brecht, Benjamin; Silberhorn, Christine (PRX Quantum)
Keywords: General Physics and Astronomy; Mathematical Physics; Applied Mathematics; Electronic; Optical and Magnetic Materials; Electrical and Electronic Engineering; General Computer Science

Multi-FPGA Designs and Scaling of HPC Challenge Benchmarks via MPI and Circuit-Switched Inter-FPGA Networks - Meyer, Marius; Kenter, Tobias; Plessl, Christian (ACM Transactions on Reconfigurable Technology and Systems)
While FPGA accelerator boards and their respective high-level design tools are maturing, there is still a lack of multi-FPGA applications, libraries, and not least, benchmarks and reference implementations towards sustained HPC usage of these devices. As in the early days of GPUs in HPC, for workloads that can reasonably be decoupled into loosely coupled working sets, multi-accelerator support can be achieved by using standard communication interfaces like MPI on the host side. However, for performance and productivity, some applications can profit from a tighter coupling of the accelerators. FPGAs offer unique opportunities here when extending the dataflow characteristics to their communication interfaces. In this work, we extend the HPCC FPGA benchmark suite by multi-FPGA support and three missing benchmarks that particularly characterize or stress inter-device communication: b_eff, PTRANS, and LINPACK. With all benchmarks implemented for current boards with Intel and Xilinx FPGAs, we established a baseline for multi-FPGA performance. Additionally, for the communication-centric benchmarks, we explored the potential of direct FPGA-to-FPGA communication with a circuit-switched inter-FPGA network that is currently only available for one of the boards. The evaluation with parallel execution on up to 26 FPGA boards makes use of one of the largest academic FPGA installations.
Keywords: General Computer Science

Steady-State Error Compensation for Reinforcement Learning-Based Control of Power Electronic Systems - Weber, Daniel; Schenke, Maximilian; Wallscheid, Oliver (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science; Electrical and Electronic Engineering

NELLIE: Never-Ending Linking for Linked Open Data - Ahmed, Abdullah Fathi; Sherif, Mohamed Ahmed; Ngomo, Axel-Cyrille Ngonga (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science; Electrical and Electronic Engineering

Predicting the development of digital media PCK/TPACK: The role of PCK, motivation to use digital media, interest in and previous experience with digital media - Schubatzky, Thomas; Burde, Jan-Philipp; Große-Heilmann, Rike; Haagen-Schützenhöfer, Claudia; Riese, Josef; Weiler, David (Computers & Education)
Keywords: Education; General Computer Science

Predicting the development of digital media PCK/TPACK: The role of PCK, motivation to use digital media, interest in and previous experience with digital media - Schubatzky, Thomas; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Haagen-Schützenhöfer, Claudia; Riese, Josef; Weiler, David (Computers & Education)
Keywords: Education; General Computer Science

Performance and Usability Evaluation of Brainwave Authentication Techniques with Consumer Devices - Arias-Cabarcos, Patricia; Fallahi, Matin; Habrich, Thilo; Schulze, Karen; Becker, Christian; Strufe, Thorsten (ACM Transactions on Privacy and Security)
Brainwaves have demonstrated to be unique enough across individuals to be useful as biometrics. They also provide promising advantages over traditional means of authentication, such as resistance to external observability, revocability, and intrinsic liveness detection. However, most of the research so far has been conducted with expensive, bulky, medical-grade helmets, which offer limited applicability for everyday usage. With the aim to bring brainwave authentication and its benefits closer to real world deployment, we investigate brain biometrics with consumer devices. We conduct a comprehensive measurement experiment and user study that compare five authentication tasks on a user sample up to 10 times larger than those from previous studies, introducing three novel techniques based on cognitive semantic processing. Furthermore, we apply our analysis on high-quality open brainwave data obtained with a medical-grade headset, to assess the differences. We investigate both the performance, security, and usability of the different options and use this evidence to elicit design and research recommendations. Our results show that it is possible to achieve Equal Error Rates as low as 7.2% (a reduction between 68–72% with respect to existing approaches) based on brain responses to images with current inexpensive technology. We show that the common practice of testing authentication systems only with known attacker data is unrealistic and may lead to overly optimistic evaluations. With regard to adoption, users call for simpler devices, faster authentication, and better privacy.
Keywords: Safety; Risk; Reliability and Quality; General Computer Science

Dequantizing the Quantum Singular Value Transformation: Hardness and Applications to Quantum Chemistry and the Quantum PCP Conjecture - Gharibian, Sevag; Le Gall, François (SIAM Journal on Computing)
Keywords: General Mathematics; General Computer Science

Server Cloud Scheduling - Maack, Marten; Meyer auf der Heide, Friedhelm; Pukrop, Simon (Algorithmica)
Abstract Consider a set of jobs connected to a directed acyclic task graph with a fixed source and sink. The edges of this graph model precedence constraints and the jobs have to be scheduled with respect to those. We introduce the server cloud scheduling problem, in which the jobs have to be processed either on a single local machine or on one of infinitely many cloud machines. For each job, processing times both on the server and in the cloud are given. Furthermore, for each edge in the task graph, a communication delay is included in the input and has to be taken into account if one of the two jobs is scheduled on the server and the other in the cloud. The server processes jobs sequentially, whereas the cloud can serve as many as needed in parallel, but induces costs. We consider both makespan and cost minimization. The main results are an FPTAS for the makespan objective for graphs with a constant source and sink dividing cut and strong hardness for the case with unit processing times and delays.
Keywords: Applied Mathematics; Computer Science Applications; General Computer Science

Spectral and Energy Efficiency Maximization of MISO STAR-RIS-Assisted URLLC Systems - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard A. (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science; Electrical and Electronic Engineering

A novel indicator for sustainability in production planning using Center of Gravity-based assessment of Pareto fronts - Hilbert, Markus; Dellnitz, Andreas; Kleine, Andreas; Tavana, Madjid (Computers & Industrial Engineering)
Keywords: General Engineering; General Computer Science

Privacy-centered authentication: A new framework and analysis - Robles-González, Antonio; Arias Cabarcos, Patricia; Parra-Arnau, Javier (Computers & Security)
Keywords: Law; General Computer Science

Computation on Encrypted Data Using Dataflow Authentication - Fischer, Andreas; Fuhry, Benny; Kußmaul, Jörn; Janneck, Jonas; Kerschbaum, Florian; Bodden, Eric (ACM Transactions on Privacy and Security)
Encrypting data before sending it to the cloud ensures data confidentiality but requires the cloud to compute on encrypted data. Trusted execution environments, such as Intel SGX enclaves, promise to provide a secure environment in which data can be decrypted and then processed. However, vulnerabilities in the executed program give attackers ample opportunities to execute arbitrary code inside the enclave. This code can modify the dataflow of the program and leak secrets via SGX side channels. Fully homomorphic encryption would be an alternative to compute on encrypted data without data leaks. However, due to its high computational complexity, its applicability to general-purpose computing remains limited. Researchers have made several proposals for transforming programs to perform encrypted computations on less powerful encryption schemes. Yet current approaches do not support programs making control-flow decisions based on encrypted data. We introduce the concept of dataflow authentication (DFAuth) to enable such programs. DFAuth prevents an adversary from arbitrarily deviating from the dataflow of a program. Our technique hence offers protections against the side-channel attacks described previously. We implemented two flavors of DFAuth, a Java bytecode-to-bytecode compiler, and an SGX enclave running a small and program-independent trusted code base. We applied DFAuth to a neural network performing machine learning on sensitive medical data and a smart charging scheduler for electric vehicles. Our transformation yields a neural network with encrypted weights, which can be evaluated on encrypted inputs in \( 12.55 \,ms \) . Our protected scheduler is capable of updating the encrypted charging plan in approximately 1.06 seconds.
Keywords: Safety; Risk; Reliability and Quality; General Computer Science

Mincut Sensitivity Data Structures for the Insertion of an Edge - Baswana, Surender; Gupta, Shiv; Knollmann, Till (Algorithmica)
Keywords: Applied Mathematics; Computer Science Applications; General Computer Science

Abnormal geodesics in 2D-Zermelo navigation problems in the case of revolution and the fan shape of the small time balls - Bonnard, B.; Cots, O.; Gergaud, J.; Wembe Moafo, Boris Edgar (Systems & Control Letters)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; General Computer Science; Control and Systems Engineering

An automated approach for developing neural network interatomic potentials with FLAME - Mirhosseini, Hossein; Tahmasbi, Hossein; Kuchana, Sai Ram; Ghasemi, Alireza; Kühne, Thomas (Computational Materials Science)
Keywords: Computational Mathematics; General Physics and Astronomy; Mechanics of Materials; General Materials Science; General Chemistry; General Computer Science

I-AID: Identifying Actionable Information From Disaster-Related Tweets - Zahera, H.M.A; Jalota, Rricha; Sherif, Mohamed Ahmed; Ngomo, Axel-Cyrille Ngonga (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science

Distributed Algorithms for Spectral and Energy-Efficiency Maximization of K-User Interference Channels - Soleymani, Mohammad; Santamaria, Ignacio; Schreier, Peter J. (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science

Algorithmic Enumeration of Ideal Classes for Quaternion Orders - Kirschmer, Markus; Voight, John (SIAM Journal on Computing)
We provide algorithms to count and enumerate representatives of the (right) ideal classes of an Eichler order in a quaternion algebra defined over a number field. We analyze the run time of these algorithms and consider several related problems, including the computation of two-sided ideal classes, isomorphism classes of orders, connecting ideals for orders, and ideal principalization. We conclude by giving the complete list of definite Eichler orders with class number at most 2.
Keywords: General Mathematics; General Computer Science

Denesting by Bounded Degree Radicals - Blömer, J. (Algorithmica)
Keywords: Applied Mathematics; Computer Science Applications; General Computer Science